The Relationship of Clean and Healthy School Living Behavior and the Incidence of Dengue Fever in Students of SMPN 1 Pancur Batu, Deli Serdang - Nanda, Meutia; Munthe, Ni'matul Ulya; Nasution, Nurul Indah; Hasibuan, Rafiqoh; Aisyah, Siti Nur; Wulandari, Tri (PROMOTOR, 2024)
Dengue hemorrhagic fever is a disease caused by the dengue virus and spread by the Aedes Aegypti mosquito. DHF cases in Indonesia in 2022 will continue to increase by 131,265 cases, while in North Sumatra in 2022 they will increase by 2,923 cases and in Deli Serdang Regency in 2022 they will increase by 803 cases. Poor PHBS (Clean and Healthy Living Behavior) is one of the causes of dengue fever transmission. The aim of this research was to determine the relationship between PHBS and the incidence of dengue fever in students at SMPN 1 Pancur Batu, Deli Serdang. This research is quantitative research with a questionnaire instrument and uses the Chi Square Test method. The population of this study were all students of SMPN 1 Pancur Batu, Deli Serdang with a sample of 85 respondents. The research results show the characteristics of respondents in terms of gender with the majority being 50 respondents (58.8%) women and 35 men (41.2%). In the behavior variable of washing hands using running water at school, the p value = 0.222, the behavior of eradicating mosquito larvae at school has a p value = 0.006, the behavior of throwing away rubbish at school has a p value = 0.001, and the behavior of cleaning the bathtub at school has a p value. = 0.000. Concluded and the variables that were related to the incidence of dengue fever were the behavior variable for eradicating mosquito larvae at school, the behavior variable for throwing away rubbish at school, and the behavior variable for cleaning bathtubs at school.